Naturalizing laboratory mice by housing in a farmyard-type habitat confers protection against colorectal carcinogenesis. (1st January 2021) - Arnesen, Henriette; Hitch, Thomas C. A.; Steppeler, Christina; Müller, Mette Helen Bjørge; Knutsen, Linn Emilie; Gunnes, Gjermund; Angell, Inga Leena; Ormaasen, Ida; Rudi, Knut; Paulsen, Jan Erik; Clavel, Thomas; Carlsen, Harald; et al.
ABSTRACT: Living in a farm environment in proximity to animals is associated with reduced risk of developing allergies and asthma, and has been suggested to protect against other diseases, such as inflammatory bowel disease and cancer. Despite epidemiological evidence, experimental disease models that recapitulate such environments are needed to understand the underlying mechanisms. In this study, we show that feralizing conventional inbred mice by continuous exposure to a livestock farmyard-type environment conferred protection toward colorectal carcinogenesis. Two independent experimental approaches for colorectal cancer induction were used; spontaneous (Apc Min/+ mice on an A/J background) or chemical (AOM/DSS). In contrast to conventionally reared laboratory mice, the feralized mouse gut microbiota structure remained stable and resistant to mutagen- and colitis-induced neoplasia. Moreover, the feralized mice exhibited signs of a more mature immunophenotype, indicated by increased expression of NK and T-cell maturation markers, and a more potent IFN-γ response to stimuli. In our study, hygienically born and raised mice subsequently feralized post-weaning were protected to a similar level as life-long exposed mice, although the greatest effect was seen upon neonatal exposure. Collectively, we show protective implications of a farmyard-type environment on colorectal cancer development and demonstrate the utility of a novel animal modeling approach that recapitulates realistic disease responses in a naturalized mammal. Graphical abstract: uf0001